Metacognitive Strategies Instruction and Its Relationship with Listening Anxiety and Listening Comprehension - Buyun Khulel (Edulitics (Education, Literature, and Linguistics) Journal, 2021)
ABSTRACT: This present paper aims at investigating the relationship between metacognitive strategies and its relationship with listening anxiety and listening comprehension. This paper summarizes the results of previous studies (Golehi, 2012) revealing that listening anxiety had negative correlation with listening comprehension and listening strategy use. The previous study (Golehi, 2012) shows that listening strategy used by learners plays an important part in reducing learners’ listening anxiety and improving learners’ listening comprehension. This paper will concern more on outlining metacognitive strategies and its relationship with listening anxiety and listening comprehension. The findings of this paper gained from some previous researches concerning in metacognitive strategies and its implication, particularly in listening comprehension.